2021
DOI: 10.1002/ese3.843
|View full text |Cite
|
Sign up to set email alerts
|

Back contacts materials used in thin film CdTe solar cells—A review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 227 publications
(202 reference statements)
4
37
0
Order By: Relevance
“…On the other hand, stable n-type doping up to n = 10 18 cm −3 has been demonstrated using indium [28], this being close to the degenerate doping density and comfortably exceeding the levels required in PV devices. Secondly, contacting is a well-known issue for p-CdTe [29], and may create a back-contact barrier (from band line ups [30] or Fermi level pinning [31]) which limits the forward bias current of the devices [32]. Strategies, such as using ZnTe:Cu [33], are required to mitigate this barrier by supplying high local p-doping near the contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, stable n-type doping up to n = 10 18 cm −3 has been demonstrated using indium [28], this being close to the degenerate doping density and comfortably exceeding the levels required in PV devices. Secondly, contacting is a well-known issue for p-CdTe [29], and may create a back-contact barrier (from band line ups [30] or Fermi level pinning [31]) which limits the forward bias current of the devices [32]. Strategies, such as using ZnTe:Cu [33], are required to mitigate this barrier by supplying high local p-doping near the contact.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies, such as using ZnTe:Cu [33], are required to mitigate this barrier by supplying high local p-doping near the contact. Nevertheless, contacting to p-CdTe solar cells is found to be universally problematic, and a recent review identified more than 70 different strategies for making the contacts [29]. Whatever the origin of the difficulties for contacting p-CdTe, they are not an issue with n-type material, for which indium is known to give a low-resistance Ohmic contact [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, back contacts with high metal work functions are economically viable materials for solar cell designs. 43 Accordingly, lower efficiencies are recorded when the metal work functions of the back contact are low since there exist high-energy Schottky barriers. Back contacts with metal work functions above 5.1 eV are considered robust for better cell performance.…”
Section: Effect Of Metal Work Function On Cell Performancementioning
confidence: 99%
“…Notably, carbon/nickel (5.0 eV) and palladium (5.3 eV) are feasible candidates for back contacts since their metal work functions are sufficiently high energy to minimize Schottky barriers, hence high PV performance. 43 Therefore, this study proposes the use of carbon/nickel (5.0 eV) and palladium (5.3 eV) as dye regenerating candidates in ssDSSCs because of their decent work functions in addition to economic viability.…”
Section: Effect Of Metal Work Function On Cell Performancementioning
confidence: 99%
“…[3,12] Other Cu-containing materials that have been considered as back contacts include Cu x Te, [13] Cu x S, [14] HgTe:Cu, CuI, CuSCN, and Cu x Zn 1−x S. [13,14,15] Copper is commonly used to dope CdTe p-type in the 10 14 -10 15 cm −3 range. [8] The Cu ions in the back contacts, including ZnTe:Cu, are known to diffuse into CdTe, and substitute Cd to form shallow acceptor states (p-type doping). However, "excess" Cu in CdTe is also associated with metastability and long-term performance degradation, including changes in the series resistance and fill factor.…”
Section: Introductionmentioning
confidence: 99%